Occupational sitting time and risk of all-cause mortality among Japanese workers - Hiroyuki Kikuchi; Shigeru Inoue; Yuko Odagiri; Manami Inoue; Norie Sawada; Shoichiro Tsugane (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: Prolonged sitting is a health risk for cardiovascular diseases and all-cause mortality, independent of moderate-to-vigorous physical activity. Epidemiological evaluation of occupational sitting has received little attention, even though it may have a potential impact on workers' health. We prospectively examined the association between occupational sitting time and all-cause mortality. METHODS: Community-dwelling, Japanese workers aged 50-74 years who responded to a questionnaire in 2000-2003 were followed for all-cause mortality through 2011. Cox proportional hazard models were employed to calculate hazard ratios (HR) of all-cause mortality among middle (1 to <3 hours/day) or longer (≥≥3 hours/day) occupationally sedentary subjects by gender or types of engaging industry ("primary industry" and "secondary or tertiary industry"). RESULTS: During 368 120 person-years of follow-up (average follow-up period, 10.1 years) for the 36 516 subjects, 2209 deaths were identified. Among workers in primary industry, longer duration of occupational sitting was significantly or marginally associated with higher mortality [HR 1.23, 95% confidence interval (95% CI) 1.00-1.51 among men; HR 1.34, 95% CI 0.97-1.84 among women]. No associations were found among secondary or tertiary industry workers (men: HR 0.87, 95% CI 0.75-1.01; women: HR 1.03, 95% CI 0.77-1.39). CONCLUSIONS: Occupational sitting time increased all-cause mortality among primary industry workers, however similar relationships were not observed for secondary-tertiary workers. Future studies are needed to confirm detailed dose-response relationships by using objective measures. In addition, studies using cause-specific mortality data would be important to clarify the physiological underlying mechanism.